Fostering Positive Communities: A Scoping Review of Community-Level Positive Psychology Interventions - Montiel, Corentin; Radziszewski, Stephanie; Prilleltensky, Isaac; Houle, Janie (Frontiers in Psychology, 2021)
Historically, positive psychology research and practice have focused on studying and promoting well-being among individuals. While positive psychology interventions focusing on the well-being of communities and marginalized groups have recently been developed, studies reporting on their nature and characteristics are lacking. The aim of this paper is to examine the nature of community-level positive psychology interventions. It reviews the target populations, intervention modalities, objectives, and desired effects of 25 community-level positive psychology interventions found in 31 studies. This scoping review shows that community-level programs based on positive psychology vary greatly in all these aspects. However, most interventions are aimed at individual-level changes to achieve target group outcomes. Contextual issues such as social conditions, values, and fairness affecting well-being are rarely considered. Discrepancies between community-level positive psychology interventions and community psychology in terms of values and social change are discussed.